Scientometric Study of Growth Patterns, Collaboration and Diffusion of Educational Psychology Knowledge in Southeast Asia 2015-2025 - Muhammad Hisyam Syafii; Nur Khofifah Saadiah; Husain Azhari; Rudyn Alaldaya; Sardorbek Ibragimov (Universitas Sebelas Maret, 2025)
This study examines the growth trends, partnerships, and distribution of educational psychology knowledge in Southeast Asia from 2015 to 2025 via a scientometric methodology. Data were derived from 400 papers indexed in Scopus and Web of Science, examined using bibliometric analysis, social network analysis, and thematic analysis utilizing VOSviewer 1.6.18 software. The findings indicated three stages of publication evolution: a stable initial growth phase (2015-2017) averaging 31 publications annually, a decline phase (2018-2019) attributed to the diversification of research methodologies, and an accelerated growth phase (2020-2025) catalyzed by the digital transformation following the COVID-19 pandemic. Co-word network analysis revealed five primary thematic clusters: learning and pedagogy (blue cluster), educator psychological well-being (red cluster), preventive psychological interventions (orange cluster), digital learning and mental health (green cluster), and cross-country studies (brown cluster). The primary issue with this research is the lack of a thorough grasp of the trends in the development, cooperation, and sharing of information in educational psychology in Southeast Asia. Productivity gaps across nations, a lack of institutional integration, and a lack of local context adaptation to global paradigms are some of the issues that need to be addressed. The findings of this study point to the need for a more coordinated approach to international research cooperation, bolstering research capabilities in developing nations, and incorporating digital technology into the transmission of information. The practical ramifications include the need for regional policies that promote researcher interaction, expand access to scientific publications, and provide culturally responsive educational psychology courses. The Psychological Bulletin achieved the top ranking with 691 citations and an annual impact factor of 86.38. The distribution pattern has a core-periphery structure, with the essential ideas of